Al-Ghazzali's Contributions to Sufism: A Comprehensive Analysis of His Spiritual Philosophy and Ethical Framework - K M A Ahamed Zubair (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Imam Al-Ghazzali (1058–1111 CE), known as